2013
DOI: 10.1097/01.pra.0000430505.52391.48
|View full text |Cite
|
Sign up to set email alerts
|

Treating the “Unhealthy Alcohol User” on Medical Wards

Abstract: Current evidence suggests the need for additional research in this area with a view toward clarifying AUD treatment guidelines for medically ill inpatients. The hospital stay could provide a valuable opportunity to initiate interventions for AUDs with medically ill patients, leading to significant changes in alcohol use behaviors and better health-related outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…AUDs and depressive symptoms may both contribute to non-adherence, and from a purely clinical perspective, it is therefore essential to screen for and treat both disorders simultaneously in order to optimize treatment outcomes. This is particularly relevant since both disorders are under-diagnosed [80,81] and under-treated[82,83] in clinical settings, yet they are amenable to behavioral and/or pharmacotherapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…AUDs and depressive symptoms may both contribute to non-adherence, and from a purely clinical perspective, it is therefore essential to screen for and treat both disorders simultaneously in order to optimize treatment outcomes. This is particularly relevant since both disorders are under-diagnosed [80,81] and under-treated[82,83] in clinical settings, yet they are amenable to behavioral and/or pharmacotherapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Cross‐sectional studies have shown that problem drinking is around 2‐ to 3‐fold more common among hospital inpatients than among the general population (Foy and Kay, ; Kouimtsidis et al., ; Reynaud et al., ). However, despite the potential and feasibility of alcohol screening, brief intervention and referral to treatment within hospitals (McQueen et al., ; Rivest et al., ; Rumpf et al., ; Smothers et al., ), detection rates of problem drinking in these settings remain low (Fagan et al., ; Rosón et al., ; Smothers et al., ). It is, therefore, paramount to further improve ways to identify high‐risk problem drinkers among patients admitted to hospitals (Fagan et al., ; NCEPOD, ).…”
mentioning
confidence: 99%
“…Additionally, in the hospital, the medical inpatient admission to manage alcohol withdrawal also offers an opportunity to assess motivation for sobriety and make plans for addiction treatment and sober support (13). A consult-liaison psychiatrist could further explore underlying and comorbid mood and anxiety disorders that would be critical to identify as treatment of these conditions can help stabilize the AUD.…”
Section: Screening Tools To Identify and Intervene On Audmentioning
confidence: 99%